Assessment of clinically significant portal hypertension by two‐dimensional shear wave elastography. (26th January 2022) - Grgurevic, Ivica; Madir, Anita; Trkulja, Vladimir; Bozin, Tonci; Aralica, Gorana; Podrug, Kristian; Mikolaševic, Ivana; Tsochatzis, Emmanuel; O'Beirne, James; Pinzani, Massimo
Abstract: Background and aims: To evaluate two‐dimensional shear wave elastography (2DSWE) in parallel with transient elastography (TE) for diagnosing clinically significant portal hypertension (CSPH) and high‐risk varices (HRV) in patients with chronic liver disease. Patients and methods: Consecutive patients with suspicion of compensated advanced chronic liver disease (cACLD) [liver stiffness measurement (LSM) ≥ 10 kPa by TE, or morphological signs suggestive of cACLD on imaging], with no history of liver decompensation, underwent hepatic venous pressure gradient (HVPG) measurement, transjugular liver biopsy and esophagogastroduodenoscopy, which served as the reference methods for diagnosing CSPH, cACLD and HRV. All patients underwent LSM and spleen stiffness measurements (SSM) by 2DSWE and TE. Results: Seventy‐six (76) patients were included (78% men, mean age 62 years, body mass index 28.3 kg/m 2, 36.8% alcoholic, 30.3% non‐alcoholic fatty liver disease, 14.5% viral hepatitis). Of them, 80.3%, 69.7%, 52.6% and 22.4% had cACLD, cirrhosis, CSPH and HRV respectively. LSM performed better than SSM in diagnosing CSPH and HRV. For CSPH, AUROCs (0.926 vs. 0.866), optimal cut‐offs (20.1 vs. 20.2 kPa) and sensitivity/specificity (80.5%/94.3% vs. 77.5% /86.1%) were comparable for 2DSWE and TE. Ruling‐out of CSPH by 2DSWE (LSM at cut‐off with ≥90% sensitivity (13.5 kPa) and platelets ≥ 150 x 10 9 /L) performed comparably to TE, with 1/24 cases falsely classified as negative. For HRV, AUROCs were similar (0.875 2DSWE, 0.851 TE) with similar optimal LSM cut‐offs enabling 100% sensitivity and ruling‐out HRV. Conclusion: Liver stiffness measurement by 2DSWE appears to perform equally well as TE for diagnosing CSPH and ruling‐out HRV in compensated chronic liver disease.